PENGARUH KUALITAS WEBSITE TERHADAP KEBERLANJUTAN PENGGUNA BERDASARKAN KEPUASAN PADA TRAVELOKA DAN AGODA - Hoe, Anthony; Palumian, Yonathan (BISMA: Jurnal Bisnis dan Manajemen, 2024)
Online flight and hotel ticket booking services are increasingly being used by Indonesians. There are several online travel platforms in Indonesia with the highest number of users, namely Traveloka and Agoda. This research aims to determine the effect of design and service quality on user satisfaction. User satisfaction will later be tested to see whether it influences website reuse intentions. In the presence of a moderating variable, interactions will be tested together with other variables. This research was conducted by providing an online survey to Agoda & Traveloka users with the sampling technique used was non-random with accidental sampling so that 120 respondents were obtained. The data analysis method used is SEM-PLS. The research results show that design quality influences satisfaction. Satisfaction influences website reuse intentions. However, interaction does not act as a mediator between these variables. These results can then be used as a reference for online utilization and improving the quality of websites in business.